KUALITAS PELAYANAN BRT TRANS SEMARANG KORIDOR II RUTE TERBOYO-SISEMUT ANALISIS SURVEI KEPUASAN MASYARAKAT ( STUDI EVALUASI ) - Deevaa Andri Putra S; Nina Widowati (Journal of Public Policy and Management Review, 2016)
To measure the quality of service ini BRT Trans Semarang corridor II route Terboyo-Sisemut use the scope in community satisfaction survey on PERMENPAN No. 16 of 2014 and compare it with the size of the service quality by Brown in Moenir (1998 in Hardiyansyah. 2011; 51) namely Reability, Assurance, Empathy, Responsiveness, Tangible. This study aimed to describe the quality of the services provided by BRT Trans Semarang corridor II ruote Terboyo-Sisemut to the community. Describing the community satisfaction with the services provided. This study uses informants namely BLU BRT Trans Semarang employees and BRT Trans Semarang Koridor II passenger as the service users. The services provided can be said is good but not maximum , it can be seen that the service provided is timely , officers also know well the things which become obligations when carrying out the task . Shelter was designed in order to provide convenience to the disabilities to receive services . . Officers also prioritize pregnant women and the elderly in getting services . Told not maximized due to the lack of publication of the BRT Trans Semarang will be the means for complaints suggestions and input . Shelter care is not good, and the double-duty officer who carried on the bus . Less maximum service can be covered by maintenance and improvements to the shelter are less suitable for use , do the publicity about their means of complaint suggestions and feedback and put stickers appeal to prioritize pregnant women and the elderly get a seat on the bus and supervision on the standard greeting is done attendant